2013
DOI: 10.1177/0734282913502937
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity and Accuracy of Oral Reading Fluency for English Learners

Abstract: The predictive validity and accuracy of an oral reading fluency (ORF) measure for a statewide assessment in English language arts was examined for second-grade native English speakers (NESs) and English learners (ELs) with varying levels of English proficiency. In addition to comparing ELs with native English speakers, the impact of English proficiency was examined among ELs. The results suggest that the predictive validity of ORF is stronger for native English speakers than for ELs. ORF scores for ELs with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Consistent with prior studies (e.g., Fien et al, 2008;Lesaux & Siegel, 2003;Vanderwood et al, 2008), moderate to high correlations were found for NWF and WIF scores with respect to reading outcomes for the entire sample, as well as for the B/EI and Intermediate English proficiency groups. The relationship between PSF and reading outcomes was much smaller.…”
Section: Predictive Validity Of Screening Measuressupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with prior studies (e.g., Fien et al, 2008;Lesaux & Siegel, 2003;Vanderwood et al, 2008), moderate to high correlations were found for NWF and WIF scores with respect to reading outcomes for the entire sample, as well as for the B/EI and Intermediate English proficiency groups. The relationship between PSF and reading outcomes was much smaller.…”
Section: Predictive Validity Of Screening Measuressupporting
confidence: 85%
“…In a study by Vanderwood et al (2008) with a sample of Spanish-speaking ELLs, first-grade NWF scores were found to be correlated with third-grade reading outcomes. In another study by Fien et al (2008) with native English speakers and Spanish-speaking ELLs, moderate correlations were found between kindergarten NWF scores and first-or second-grade reading outcomes.…”
Section: Predictive Validity Of Early Literacy Screening Toolsmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, the NWF probes were modeled after that of an existing standardized measure (DIBELS NWF; Good and Kaminski 2002), but they were not piloted or validated by previous research using NWF for this study's specific purposes. Furthermore, the average interscorer agreement was lower than the standard of at least 95 % accuracy in scoring of errors for NWF tasks as established by previous studies (Fuchs et al 2004;Vanderwood et al 2008).…”
Section: Discussionmentioning
confidence: 67%
“…Although the psychometrics of these specific curricular assessments have not been researched extensively, there is an increasing body of research to support the reliability and validity of similar types of curriculum-based measurement reading assessments (see Reschly, Busch, Betts, Deno, & Long, 2009;Vanderwood, Kinklater, & Healy, 2008).…”
Section: Study Limitationsmentioning
confidence: 99%